Fruit and vegetable consumption, Helicobacter pylori antibodies, and gastric cancer risk: A pooled analysis of prospective studies in China, Japan, and Korea. Issue 3 (31st October 2016) - Wang, Tianyi; Cai, Hui; Sasazuki, Shizuka; Tsugane, Shoichiro; Zheng, Wei; Cho, Eo Rin; Jee, Sun Ha; Michel, Angelika; Pawlita, Michael; Xiang, Yong‐Bing; Gao, Yu‐Tang; Shu, Xiao‐Ou; et al.
Abstract : Epidemiological findings on the association between fruit and vegetable consumption and gastric cancer risk remain inconsistent. The present analysis included 810 prospectively ascertained non‐cardia gastric cancer cases and 1, 160 matched controls from the Helicobacter pylori Biomarker Cohort Consortium, which collected blood samples, demographic, lifestyle, and dietary data at baseline. Conditional logistic regression adjusting for total energy intake, smoking, and H. pylori status, was applied to calculate odds ratios (ORs) and 95% confidence intervals (CIs) for gastric cancer risk across cohort‐ and sex‐specific quartiles of fruit and vegetable intake. Increasing fruit intake was associated with decreasing risk of non‐cardia gastric cancer (OR = 0.71, 95% CI: 0.52–0.95, p trend = 0.02). Compared to low‐fruit consumers infected with CagA‐positive H. pylori, high‐fruit consumers without evidence of H. pylori antibodies had the lowest odds for gastric cancer incidence (OR = 0.12, 95% CI: 0.06–0.25), whereby the inverse association with high‐fruit consumption was attenuated among individuals infected with CagA‐positive H. pylori (OR = 0.82, 95% CI: 0.66–1.03). To note, the small number of H. pylori negative individuals does influence this finding. We observed a weaker, nondose‐response suggestion of an inverse association of vegetable intake with non‐cardia gastric cancer risk. High fruit intake may play a role in decreasing risk of non‐cardia gastric cancer in Asia. Abstract : What's new? Does a diet rich in fruits and vegetables affect the risk of gastric cancer (GC) in Asia? The answer has been unclear. In this prospective study, the authors found that increased fruit intake was indeed associated with a decreased risk of GC. (Vegetables were also beneficial, but to a lesser degree.) However, this impact was significantly less pronounced in people infected with H. pylori . These results suggest that increasing fruit intake may lower the risk of GC. The interaction with H. pylori should be investigated further.